The role of pelvic ultrasound for the diagnosis and management of central precocious puberty: An update - Talarico, Valentina; Rodio, Maria Benedetta; Viscomi, Antonio; Galea, Eulalia; Galati, Maria Concetta; Raiola, Giuseppe (Acta Biomedica Atenei Parmensis, 2021)
Sexual precocity refers to the appearance of physical and hormonal signs of pubertal development at an earlier age. It may be considered as the expression of secondary sexual characteristics prior to the pubertal age In central precocious puberty (CPP), which is gonadotropin-dependent, early maturation of the entire hypothalamic-pituitary-gonadal (HPG) axis occurs, with the full spectrum of physical and hormonal changes of puberty. True precocious puberty in girls must also be distinguished from premature thelarche (PT), usually with breast development before the age of 3 years, and premature pubarche (PA), with the isolated development of pubic hair. These conditions are not usually associated with accelerated growth rate or advancement in bone age. Clinical, laboratory and instrumental evaluations are necessary for the diagnosis. Pelvic ultrasound could serve as a complementary tool for the diagnosis, treatment and follow-up of CPP. The interpretation of clinical, laboratory and strumental data must be performed by an expert pediatric endocrinologist to maximize the diagnostic value in females with pubertal disorders.